Binômio mãe-filho: estudo epidemiológico e de base populacional desenvolvido em maternidades de baixo e alto risco - Carvalheira, Ana Paula Pinho [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Objectives: a) Describe the adequacy of prenatal care site, according to gestational risk factors. b) Identify factors associated with maternal and perinatal outcome in pregnant women with hypertension; c) Compare the sociodemographic characteristics of the pregnant women, the care given to the mother-child binomial at delivery and conditions of newborns at birth in public and private hospitals. Method: This is an epidemiological, observational study conducted with a total of 1343 pregnant women in a medium sized city in the state of São Paulo - Brazil, whose deliveries occurred from January to June 2012. Using instruments built specifically for this study, containing the variables of interest. Results: Of the 291 pregnant women/mothers who were attended at high risk prenatal, 131 (45.0 %) had no indication for such and should be being followed in primary care or private services. Women who had previous medical conditions that indicated specialized follow-up, totaled 39 cases and 19 (48.7 %) received this type of care. Among the risk factors of current pregnancy that require referral to high risk, were 198 cases, of which 90 (45.5%) were followed in this level of complexity. There were 31 at high risk (39.2%) of the 79 cases classified as requiring referral to urgent/emergency obstetric care. The group of hypertensive disorders was the group most frequently kept in primary care, despite having an indication of high risk prenatal for disease prior to pregnancy, illness during the pregnancy or urgent/emergency condition. As for maternal factors associated with hypertension, the only socio-demographic variable with the association was the age older than 35 years (OR = 1.64, 95% CI 1.02 to 2.64, p = 0.043); independently, it was observed among women who had hypertension during pregnancy, a higher rate of neonatal resuscitation (OR = 2.24, 95% CI 1.31 to 3.83, p = 0.003), preterm birth (OR = 3.47, 95% CI 2.09 to 5.77 and p <0.001) and low birth weight (OR = 2.33, 95% CI 1.33 to 4.09, p = 0.003). There was a positive association between giving birth in a public hospital and being a teenager (OR = 4.21, CI = 2.64 to 6.73), having elementary education (OR = 10.9, CI = 6.94 to 17.39), being primiparous (OR = 1.54, CI = 1.21 to 1.96), not having a partner (OR = 2.65, CI = 1.74 to 4.04), having unplanned pregnancy (OR = 3.23, CI = 2.51 to 4.15), having held up to six prenatal consultations (OR = 3.10, CI = 2.04 to 3.23) and having prenatal care in public service (OR = 49.75, CI 32.80 to 75.47). As for care during labor, birth in a public hospital was protected from performing cesarean delivery and elective caesarean section (OR = 0.001, CI = 0.0004 to 0.006) and other routine procedures, whose evidence points losses. Showed a significant association between birth in the public hospital and adverse neonatal outcomes, including prematurity (OR = 1.63, CI = 1.12 to 2.36), low birth weight (OR = 2.26, CI = 1.46-3, 51) and need for resuscitation (OR = 3.32, CI = 1.97 to 5.59). Even with these negative conditions, born in the public hospital favored the exclusive breastfeeding at discharge. Conclusion: It is important to identify the gestational risk factors as early as possible, promoting agility in service, defining the need for care and technological density that should be offered to users at all times. Women over 35 require even more care during the prenatal follow-up for early detection of pressure changes. Controlling the hypertensive disorders in pregnancy and intervening in a timely manner may result in no maternal complications and health problems in the fetus. Both the public and the private hospitals, there have been aspects that deserve and effective measures and actions by health professionals, as well as managers, envisisioning the success of maternal and child care, especially with regard to better neonatal outcomes.

Objetivos: a) Descrever a adequação do local de assistência pré-natal, segundo fatores de risco gestacional. b) Identificar fatores maternos associados e o resultado perinatal de gestantes com hipertensão; c) Comparar as características sociodemográficas das parturientes, a atenção desenvolvida ao binômio mãe-bebê no momento do parto e as condições dos neonatos ao nascer em hospitais público e privado. Método: Trata-se de estudo epidemiológico, observacional, realizado com população de parturientes de município de médio porte do interior do Estado de São Paulo - Brasil, cujos partos ocorreram de janeiro a junho de 2012, totalizando 1343 mulheres. Utilizou-se instrumento construído especialmente para este estudo, contendo as variáveis de interesse. Resultados: Das 291 gestantes/parturientes atendidas no pré-natal de alto risco, 131 (45,0%) não tinham indicação para tal e deveriam estar sendo acompanhadas na atenção básica ou serviços privados. As mulheres que apresentavam condições clínicas prévias que indicavam seguimento especializado, totalizaram 39 casos e 19 (48,7%) recebiam esse tipo de atendimento. Entre os fatores de risco da gestação atual que requerem encaminhamento ao alto risco, foram 198 casos, dos quais 90 (45,5%) foram seguidos neste nível de complexidade. Foram atendidos no alto risco 31 (39,2%) dos 79 casos classificados como requerendo encaminhamento para urgência/emergência obstétrica. O conjunto das síndromes hipertensivas constituiu o grupo mais frequentemente mantido na atenção básica, embora tivesse indicação de pré-natal de alto risco por doença prévia à gravidez, doença na gestação atual ou condição de urgência/emergência. Quanto aos fatores maternos associados a hipertensão, a única variável sociodemográfica com associação foi a idade superior a 35 anos (OR=1,64; IC95%=1,02-2,64 e p=0,043); de maneira independente, observou-se entre as mulheres que apresentaram síndrome hipertensiva na gestação maior chance de reanimação neonatal (OR=2,24; IC95%=1,31-3,83 e p=0,003), nascimento pré-termo (OR=3,47; IC95%=2,09-5,77 e p<0,001) e baixo peso ao nascer (OR=2,33, IC95%=1,33-4,09 e p=0,003). Houve associação positiva entre nascer no hospital público e ser adolescente (OR=4,21, IC=2,64-6,73), estudar até o ensino fundamental (OR=10,9, IC=6,94-17,39), ser primípara (OR=1,54, IC=1,21-1,96), não ter companheiro (OR=2,65, IC=1,74-4,04), não ter planejado a gestação (OR=3,23, IC=2,51-4,15), ter realizado até seis consultas pré-natais (OR=3,10, IC=2,04-3,23) e ter feito pré-natal no serviço público (OR=49,75, IC=32,80-75,47). Quanto à atenção ao parto, nascer no hospital público protegeu da realização de parto cesárea e cesárea eletiva (OR=0,001, IC=0,0004-0,006) e de outros procedimentos rotineiros, cujas evidências apontam prejuízos. Mostrou-se associação significativa entre nascer no hospital público e desfechos neonatais negativos, incluindo prematuridade (OR=1,63, IC=1,12-2,36), baixo peso (OR=2,26, IC=1.46-3,51) e necessidade de reanimação (OR=3,32, IC=1,97-5,59). Mesmo havendo essas condições negativas, nascer no hospital público favoreceu o aleitamento materno exclusivo na alta. Conclusão: É importante que se identifiquem os fatores de risco gestacional o mais precocemente possível, favorecendo a agilidade na assistência, definição da necessidade de cuidado e da densidade tecnológica que devem ser ofertadas às usuárias em cada momento. Mulheres acima de 35 requerem ainda mais cuidado no seguimento pré-natal, para identificação precoce de alterações pressóricas. Controlar as síndromes hipertensivas na gravidez e intervir no momento oportuno pode resultar em gestação sem complicações maternas e agravos à saúde do concepto. Tanto no hospital público quanto no privado verificaram-se aspectos que merecem medidas e ações efetivas de profissionais de saúde, bem como de gestores, com vistas ao sucesso da atenção materno-infantil, especialmente no que se refere a melhores desfechos neonatais.
Mother- child: epidemiological studies and population-based developed in low and high risk maternity hospitals
Keywords: Pregnancy; Epidemiology; Maternal and child health; High-risk; Risk factors; Delivery of health care; Morbidade; Saúde materno-infantil; Gravidez de alto risco; Fatores de risco; Assistência a saúde